An Unusual Case of Mammary Paget’s Disease Diagnosed Using Dynamic Contrast-Enhanced MRI - Eleonora Gaspari; Aurora Ricci; Valeria Liberto; Angela Lia Scarano; Maria Fornari; Giovanni Simonetti (Case Reports in Radiology)
Mammary Paget’s disease is a rare presentation of breast cancer. At clinical examination, it is characterized by skin lesions of the nipple-areola complex, almost always a sign of malignancy. In fact, it is often associated with an underlying mammary ductal carcinoma in situ (DCIS) or invasive carcinoma. An underlying carcinoma is also common in women with negative mammography and ultrasound (US); in these cases, magnetic resonance imaging (MRI) is a diagnostic tool useful in the detection of occult cancer. We described an unusual case of mammary Paget’s disease with underlying DCIS, in a patient without nipple-areola complex alterations and/or palpable lump. On suspicion of Paget’s disease, the patient underwent MRI examination that proved useful for an accurate diagnosis. Biopsy confirmed dynamic MRI findings.